William Carlos Williams and the American Scene, 1920-1940 - Tashjian, Dickran (New York : Whitney Museum of American Art, 1978)
Williams, William Carlos ; Léger, Fernand ; Matisse, Henri ; Hartley, Marsden ; Demuth, Charles ; Sheeler, Charles ; Billings, Henry ; Davis, Stuart ; Crawford, Ralston ; O'Keeffe, Georgia ; Marin, John ; Zorach, William ; Shahn, Ben ; Wood, Grant ; etc.
William Carlos Williams and the American Scene, 1920-1940, Whitney Museum of American Art, New York, December 12, 1978 - February 4, 1979
boek
Keywords: Amerika